Design of feeder route network using combined genetic algorithm and specialised repair heuristic - O'MAHONY, MARGARET MARY (National Center for Transit Research (NCTR), 2007)
In metropolitan cities an efficient integrated public transportation system is unavoidable in order to restrict unsustainable growth of private and intermediate transport modes. Well designed feeder routes and coordinated schedules to minimize transfer time from main transit to feeder buses play an important role. Past literature reveals that heuristic approach had been popular for design of routes and had been applied successfully in verities of network design problems. Non traditional optimisation technique especially Genetic Algorithms are also found to be very effective in generation of optimised feeder routes and schedules. In this research Genetic Algorithm first develops feeder routes and then a specialized heuristic Algorithm works as repair algorithm in order to satisfy demand of all the nodes. Thus the advantages of both Genetic Algorithm and Specialized Heuristic Algorithm are obtained in this method. The developed feeder route structure is found to be better in terms of load factors in buses, satisfaction of demand and waiting time for feeder buses as compared to existing scenario and earlier approaches adopted by authors far the same study area.
PUBLISHED
Keywords: urban transport system; public transport system; Genetic Algorithm